1989
DOI: 10.2337/diacare.12.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Hypoglycemia in NIDDM Patients Treated With Oral Hypoglycemic Agents

Abstract: We assessed the prevalence of hypoglycemic symptoms in patients (aged 40-65 yr) treated with oral hypoglycemic agents (OHAs) attending routine diabetes clinics at our hospital. Symptoms were experienced during the previous 6 mo in 41 of 203 (20.2%) patients treated with sulfonylureas but in none of the 16 patients treated with metformin alone. Hypoglycemic symptoms were experienced at least monthly in 5.9% and less frequently in 14.3% of patients. The prevalence of symptoms decreased with increasing duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(76 citation statements)
references
References 0 publications
5
69
1
1
Order By: Relevance
“…In contrast, metformin (odds ratio 1.42) was associated with only a small relative risk elevation, as reported previously (1,9). The proportion of patients developing documented hypoglycemia in our study population was similar to previous studies (9,11), although reported frequencies varied substantially (0 -73,000 per 100,000 person-years) (7,11,21). In our study, hypoglycemia had to be severe enough to lead to a GP or hospital visit, while minor events may have been missed.…”
Section: Hypoglycemiasupporting
confidence: 89%
“…In contrast, metformin (odds ratio 1.42) was associated with only a small relative risk elevation, as reported previously (1,9). The proportion of patients developing documented hypoglycemia in our study population was similar to previous studies (9,11), although reported frequencies varied substantially (0 -73,000 per 100,000 person-years) (7,11,21). In our study, hypoglycemia had to be severe enough to lead to a GP or hospital visit, while minor events may have been missed.…”
Section: Hypoglycemiasupporting
confidence: 89%
“…A study (75) in England of 219 people with type 2 diabetes treated with sulfonylureas and/or metformin observed that 20% of those taking sulfonylureas had experienced symptoms of hypoglycemia in the preceding 6 months. In Atlanta, a 6-month, retrospec- tive, cross-sectional survey of 1,055 predominantly female, African-American patients with type 2 diabetes, treated with oral antidiabetic drugs or insulin, completed serial questionnaires to estimate the frequency of hypoglycemia (76).…”
Section: Frequency Of Hypoglycemia In Type 2 Diabetes -Mild Hypoglycementioning
confidence: 99%
“…Early estimates of the incidences of symptomatic hypoglycaemia associated with sulphonylureas varied greatly Ð from 19 to 404 events per 1000 patient-years. 7,8 Recent data, from the UKPDS, showed that 30% of patients treated with glibenclamide reported symptomatic hypoglycaemia during the ®rst year of therapy Ð the same incidence as was experienced among insulin-treated patients. 2 With time, the incidence of hypoglycaemia decreased with sulphonylurea therapy, but so too did glycaemic control, an observation that could be taken to imply a causal relationship.…”
Section: Drug-induced Hypoglycaemia In Type 2 Diabetes: How Common?mentioning
confidence: 96%